A proposed redosing interval of del Nido cardioplegia solution in adult cardiac surgery: a propensity-matched study. (July 2021) - Koda, Yojiro; Kitahara, Hiroto; Nishida, Hidefumi; Jeevanandam, Valluvan; Ota, Takeyoshi
Background: Recently, del Nido cardioplegia solution (DN) has been utilized in adult cardiac surgery. However, adequate interval of maintenance dose(s) is still unclear. The purpose of this study was to assess the safety and efficacy of our DN protocol by comparing with conventional cold whole blood cardioplegia (CWB). Methods: A total of 1003 consecutive patients (DN group, N = 350 vs. CWB group, N = 653) underwent cardiovascular surgery between July 2013 and September 2018 were included in this study. The DN protocol was to administer 1000 to 1200 ml as an initial dose and to add maintenance dose(s) (500 ml each) every 60 minutes when the estimated cross-clamp time was over 90 minutes. CWB was given every 20 minutes, regardless of cross-clamp time. Propensity matching identified 254 matched pairs for analysis. The preoperative and postoperative data were reviewed. Results: Cross-clamp time was significantly shorter in the DN group compared with the CWB group (107 ± 56 minutes vs. 116 ± 49 minutes, p = 0.0458). A retrograde cannula was used in 124 (48.8%) patients in the DN group and 181 (71.3%) patients in the CWB group (p < 0.0001). There were no significant differences in requiring postoperative cardiac supports (inotropes, mechanical circulatory supports) and major complications. In-hospital mortality was similar between two groups (DN group: 3.2% vs. CWB group: 2.4%, p = 0.5872). Conclusions: Short-term clinical outcomes in the patients underwent cardiovascular surgery with the DN protocol including the redosing interval strategy were acceptable. Also, DN protocol was associated with shortened cross-clamp time and less usage of the retrograde cannula.